Understanding The REITs Market Development In Hong Kong And Its Future Development - Ning, Ma (2009)
This study analyzes the factors influencing the performance of REITs in Hong Kong stock exchange, figures out the factors including not only the macroeconomic variables, but also the psychology of investors, operations ways of REITs, related rules and regulations and the risk preventions sense of investors.